1996
DOI: 10.1287/isre.7.2.268
|View full text |Cite
|
Sign up to set email alerts
|

Process Structuring in Electronic Brainstorming

Abstract: One aspect of brainstorming that has received little research attention is how the brainstorming problem should be presented to the group, whether as one all-encompassing question or as a series of separate questions each focusing on one aspect of the problem. This paper reports the results of two experiments in which subjects (MBAs in the first, senior executives in the second) electronically brainstormed on intact problems (where all parts of the problem were presented simultaneously) or on decomposed proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 22 publications
8
102
1
2
Order By: Relevance
“…GSS benefits could increase with group size [30], with task difficulty [29], and with support from an facilitator [3]. Further exploration showed that performance could be further enhanced by, for example, decomposing complex problems [24], by invoking social comparison (e.g., "Groups who produce fewer ideas than this standard are below average. "), and by using humor to raise the salience of a social comparison (e.g.…”
Section: [Figure 4 About Here]mentioning
confidence: 99%
“…GSS benefits could increase with group size [30], with task difficulty [29], and with support from an facilitator [3]. Further exploration showed that performance could be further enhanced by, for example, decomposing complex problems [24], by invoking social comparison (e.g., "Groups who produce fewer ideas than this standard are below average. "), and by using humor to raise the salience of a social comparison (e.g.…”
Section: [Figure 4 About Here]mentioning
confidence: 99%
“…Thus, the current finding that idea quality in the nominal condition was significantly better (across all three quality ratings, including originality, feasibility, and effectiveness), while quantity was not significantly impacted by experimental condition, has interesting implications. As discussed by Dugosh et al (2000), high quality ideas have been commonly thought to positively correlate with idea quantity (see, e.g., Dennis, Valacich, Connolly, & Wynne, 1996;Diehl & Stroebe, 1987;Mullen et al, 1991); however, empirical support for this premise is mixed (Chidambaram & Tung, 2005, Barki & Pinsonneault, 2001, and doesn't hold within the current experimental context. Our finding underscores the need to evaluate both quality and quantity in order to determine the extent to which experimental findings extend to applied settings where quality may be paramount.…”
Section: Applied Industrial Factorsmentioning
confidence: 90%
“…Our second measure, satisfaction, evaluates the level of satisfaction of the participants with the tool. It contains 7 unweighted items from Dennis et al (2006) and Santos et al (2015) and is rated on a 5-point Likert-scale [10,33]. The third measure involves the perceived effectiveness of the process and contains four unweighted items, rated on a 5-point Likert-scale.…”
Section: Methodsmentioning
confidence: 99%